Analisis Rasio Solvabilitas Pada PT. Sido Muncul, Tbk Periode 2017-2021: Analysis Solvency Ratio at PT. Sido Muncul, Tbk Period 2017-2021 - Yuli; Vira Tandiawan (Jurnal Ilmiah Produktif, 2022)
Company’s financial performance can be assessed using financial ratios, one of them is solvency ratio. Solvency ratio is used for assessed financial performance of company in terms of in paying their debts. This research use quantitative data that is secondary data in the form of financial statements of PT. Sido Muncul, Tbk period 2017-2021 obtained from their official website taken by using the documentation technique. The result analysis data using Debt to Total Asset Ratio shows the ratio value in the periode 2017-2021 is always below the measurement standard that is <35%. The result analysis data using Debt to Equity Ratio shows the ratio value in the periode 2017-2021 is always below the measurement standard that is 90%. Value ratio below standard shows that company’s financial performance of paying their debts is good, because the lower ratio value shows the higer asset and equity value to provide the company’s debts guarantee.